Informal Entrepreneurship and Cross-Border Trade between Mozambique and South Africa (African Human Mobility Review, 2021)
Informal cross-border trading is an essential part of Maputo’s informal economy.This paper presents the results of a 2014 SAMP survey of informal entrepreneursinvolved in cross-border trade between Johannesburg and Maputo. Aquestionnaire was administered to a sample of 403 informal traders in 7 marketsin Maputo. The study showed that most of the entrepreneurs began their businessactivities as vendors and only later moved into cross-border trading. Theoverwhelming majority used their personal savings to start their business andthey face significant barriers in accessing business loans from formal bankingchannels. The study demonstrates the importance of cross-border traders to boththe Mozambican and South African economy. In South Africa, the cross-bordertraders make a significant contribution by buying local goods and utilising theservices provided by the country’s travel and hospitality industry. InMozambique, they supply affordable products to the country’s growing informalsector and play an important role in generating employment.